L'Amerique Latine : l'essor sous la republique et la liberté - Rouma, Georges. (La Renaissance du Livre)
Conteúdo: - 1. Argentina - Uruguay - Paraguay - Chili - Peru - Bolive - Equateur.- v. 2. Mexique - Guatemala - Salvador - Honduras - Nicacagua - Costa Rica - Panama - Colombia - Venezuela - Cuba - Haiti - Republique Dominicaine.